A Pandemic Perspective: Analyzing the Impact of COVID-19 on Diabetes Management and Mood Through the Lens of Location and Family Conflict. Issue 3 (June 2022) - Moore, Hailey; Abadula, Fayo; Garretson, Sydney; Okonkwo, Nkemjika; Streisand, Randi; Jaser, Sarah
Purpose: The purpose of this study was to examine the influence of COVID-19 on teens' diabetes management and mood and their association with family conflict. Methods: One hundred and nineteen teens ages 13 to 17 (M = 15.5 ± 1.3 years, 61.3% female, 57.1% non-Hispanic White) and 119 parents (83.2% female, 75.6% married, 63.9% non-Hispanic White) enrolled in an ongoing two-site randomized behavioral clinical trial. At baseline, dyads completed the Revised Diabetes Family Conflict scale and a survey measuring the impact of COVID-19 on teens' mood and diabetes management. Results: Parent- and teen-reported impacts of COVID-19 on diabetes management and teen mood were positively correlated. Higher levels of both parent- and teen-reported family conflict were associated with greater parent-reported impact of COVID-19 on diabetes management and teen mood. In addition, teen-reported impact of COVID-19 on their mood varied by geographical location but not population density. Conclusions: COVID-19 influenced teen diabetes management and mood, and the impact of COVID-19 was related to diabetes-related family conflict and differed by geographic location. Findings lend support for mental health interventions targeting teens with T1DM affected by COVID-19 and monitoring the long-term effects of the pandemic.